Analisis Faktor Yang Memengaruhi Kualitas Pelayanan Kesehatan Dengan Metode Servqual Di Puskesmas Wilayah Kerja Dinas Kesehatan Aceh Timur Tahun 2018 - Hermansyah Hermansyah; Ayi Darmana; Nur'aini Nur'aini (HEALTH CARE : JURNAL KESEHATAN, 2019)
ABSTRACT Introduction, quality health services are health services that must pay attention to four main elements. Based on the survey conducted on the services of Puskesmas to patients as many as 10 people, 6 of them felt that the quality of service in the Puskesmas was not maximal, while the other 4 stated that the service was maximal. The purpose of this study was to determine the factors that influence the quality of health services with the Servqual Method. The method, The research design used in this study was Cross Sectional. The population in this study were 7,635 people and samples taken by accidental sampling were as many as 99 people. Methods of data collection are primary data and secondary data. Data analysis used is binary logistic regression test. Results, the results showed that physical condition has a sig-p value of 0.007 <0.05, reliability of sig-p 0.008 <0.05, responsiveness of sig-p 0.011 <0.05 and sig-p guarantee of 0.034 <0.05 which means physical condition , reliability, responsiveness and assurance have an influence on the quality of health services, while caring does not have an influence on the quality of health services because it has a sig-p value of 0.325> 0.05. Suggested, It is hoped that it can become a reference for the community and for cadres in the Puskesmas to better understand the importance of quality services that are in accordance with the regulations of the health ministry to maximize health services provided to patients. Keywords : Health Service Quality Factors, Servqual Method